A Quantitative Approach Regarding the Evolution of the Romanian Tourism Firms, During and After the Global Financial Crisis - Vasile Alecsandru Strat; Adriana Ana Maria Davidescu; Raluca Mariana Grosu; Ion-Daniel Zgură (Amfiteatru Economic Journal, 2016)
The main goal of this research paper is to provide a quantitative assessment of the Romanian tourism industry (hotels and restaurants) from a county level perspective, in the specific context of the global financial recession and in the post -recession one. The evolution of the field is analyzed for the period 2008-2014 using county level data sourced from the National Institute of Statistics and from the Office of the Trade Register. The evolution of the main characteristics of the field: number of companies, number of employees, total turnover of the companies from the field and number of newly established companies, suggest the existence of significant disparities at the county level. The research reveals the fact that the total number of employees from the field (companies which have sent the final year documentation to the MPF) has decreased during the analyzed period with over 20%, fact that is a clear indicator of the magnitude of the effects of the crisis. The analysis of the disparities has revealed that Bucharest which is the most important concentration pole in this field, accounting for almost 11% from the total number of companies in 2008, has diminished its importance to little under 8.7%, in 2014. Using panel data regression we have identified some of the main characteristics of the Romanian counties that can be considered as indicators of the development perspectives of the tourism (hotels and restaurants) at county level (NUTS 3).
Keywords: L83; O18; P25; P48; 330; tourism firms; fixed/random effects; panel data regression; county level disparities; regional development